Antiinflammatory Therapy with Canakinumab for Atherosclerotic Disease - Ridker, Paul M; Everett, Brendan M; Thuren, Tom; MacFadyen, Jean G; Chang, William H; Ballantyne, Christie; Fonseca, Francisco; Nicolau, Jose; Koenig, Wolfgang; Anker, Stefan D; Kastelein, John J P; Cornel, Jan H; et al. (The New England journal of medicine, 2017)
BACKGROUND: Experimental and clinical data suggest that reducing inflammation without affecting lipid levels may reduce the risk of cardiovascular disease. Yet, the inflammatory hypothesis of atherothrombosis has remained unproved. METHODS: We conducted a randomized, double-blind trial of canakinumab, a therapeutic monoclonal antibody targeting interleukin-1β, involving 10,061 patients with previous myocardial infarction and a high-sensitivity C-reactive protein level of 2 mg or more per liter. The trial compared three doses of canakinumab (50 mg, 150 mg, and 300 mg, administered subcutaneously every 3 months) with placebo. The primary efficacy end point was nonfatal myocardial infarction, nonfatal stroke, or cardiovascular death. RESULTS: At 48 months, the median reduction from baseline in the high-sensitivity C-reactive protein level was 26 percentage points greater in the group that received the 50-mg dose of canakinumab, 37 percentage points greater in the 150-mg group, and 41 percentage points greater in the 300-mg group than in the placebo group. Canakinumab did not reduce lipid levels from baseline. At a median follow-up of 3.7 years, the incidence rate for the primary end point was 4.50 events per 100 person-years in the placebo group, 4.11 events per 100 person-years in the 50-mg group, 3.86 events per 100 person-years in the 150-mg group, and 3.90 events per 100 person-years in the 300-mg group. The hazard ratios as compared with placebo were as follows: in the 50-mg group, 0.93 (95% confidence interval [CI], 0.80 to 1.07; P=0.30); in the 150-mg group, 0.85 (95% CI, 0.74 to 0.98; P=0.021); and in the 300-mg group, 0.86 (95% CI, 0.75 to 0.99; P=0.031). The 150-mg dose, but not the other doses, met the prespecified multiplicity-adjusted threshold for statistical significance for the primary end point and the secondary end point that additionally included hospitalization for unstable angina that led to urgent revascularization (hazard ratio vs. placebo, 0.83; 95% CI, 0.73 to 0.95; P=0.005). Canakinumab was associated with a higher incidence of fatal infection than was placebo. There was no significant difference in all-cause mortality (hazard ratio for all canakinumab doses vs. placebo, 0.94; 95% CI, 0.83 to 1.06; P=0.31). CONCLUSIONS: Antiinflammatory therapy targeting the interleukin-1β innate immunity pathway with canakinumab at a dose of 150 mg every 3 months led to a significantly lower rate of recurrent cardiovascular events than placebo, independent of lipid-level lowering. (Funded by Novartis; CANTOS ClinicalTrials.gov number, NCT01327846 .).
Keywords: Male; monoklonální protilátky; infekce; ateroskleróza; cévní mozková příhoda; vztah mezi dávkou a účinkem léčiva; sekundární prevence; neutropenie; C-reaktivní protein; Stroke; Aged; interleukin-1beta; mužské pohlaví; senioři; incidence; Secondary Prevention; infarkt myokardu; humanizované monoklonální protilátky; dvojitá slepá metoda; Antibodies, Monoclonal, Humanized; Neutropenia; kardiovaskulární nemoci; lipidy; Infections; lidé; ženské pohlaví; Atherosclerosis; Humans; Myocardial Infarction; Interleukin-1beta; Lipids; C-Reactive Protein; antiflogistika; Antibodies, Monoclonal; Anti-Inflammatory Agents; Cardiovascular Diseases; Double-Blind Method; Female; Dose-Response Relationship, Drug; lidé středního věku; Incidence; Middle Aged